2021
DOI: 10.3389/fphys.2021.761691
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Drug Proarrhythmicity Using Artificial Neural Networks With in silico Deterministic Model Outputs

Abstract: As part of the Comprehensive in vitro Proarrhythmia Assay initiative, methodologies for predicting the occurrence of drug-induced torsade de pointes via computer simulations have been developed and verified recently. However, their predictive performance still requires improvement. Herein, we propose an artificial neural networks (ANN) model that uses nine multiple input features, considering the action potential morphology, calcium transient morphology, and charge features to further improve the performance o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 15 publications
(45 reference statements)
0
15
1
Order By: Relevance
“…The proposed deep CNN model can achieve better classification performance than the classical models that evaluate drug toxicity by focusing on the ion channel change caused by drugs. In addition, it showed excellent results, exceeding the performance of our other study—Yoo et al developed the ANN model using nine in silico features considering the morphological information of the AP trace and transient calcium trace, including the qNet and qInward, which are the ion net charge features 30 …”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…The proposed deep CNN model can achieve better classification performance than the classical models that evaluate drug toxicity by focusing on the ion channel change caused by drugs. In addition, it showed excellent results, exceeding the performance of our other study—Yoo et al developed the ANN model using nine in silico features considering the morphological information of the AP trace and transient calcium trace, including the qNet and qInward, which are the ion net charge features 30 …”
Section: Discussioncontrasting
confidence: 58%
“…In addition, it showed excellent results, exceeding the performance of our other study-Yoo et al developed the ANN model using nine in silico features considering the morphological information of the AP trace and transient calcium trace, including the qNet and qInward, which are the ion net charge features. 30 In several studies, the dV m /dt was identified to be helpful to detect the occurrence of TdP or the drug effects. 31,32 Because when drugs make a blockage in the ion channels, the dV m /dt in the depolarization phase is reduced; Passini et al observed the main effect of lidocaine and mexiletine to the peak sodium through a decreased maximal dV m /dt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A general issue with in silico based classifiers, such as that described here and those published as part of CiPA 16 and in other studies, 19,20 is the significant cost, time and technical burden of in vitro data collection required to inform the models-that is, the measures of potency and binding kinetics against multiple cardiac ion channels. The measurement of kinetics, in particular, has proven difficult to implement, 47 particularly on high-throughput patch clamp platforms.…”
Section: Potential For Direct Measurement From Voltage Waveformsmentioning
confidence: 99%
“…Several works have been published on the implementation of the CiPA based in silico simulations for the prediction of ventricular arrhythmia and TdP biomarkers using predicted or experimentally determined drug-induced ion channel inhibition data [11][12][13][14][15][16][17][18][19] . Computational models of human and animal electrophysiology operate at different biological levels, ranging from a single channel to whole tissue simulations and vary in terms of the degree of complexity and abstraction, the underlying mathematical approaches, and physiological parameters [11] .…”
Section: Introductionmentioning
confidence: 99%